Method for preparing electrolytic cobalt through multi-stage electrolysis
Through filtration of modified nanofiltration membrane and multiple electrolytic treatments, combined with the use of hydrogen peroxide and polyacrylamide, the problem of low purity of cobalt in the prior art is solved, and the preparation of high-purity electrolytic cobalt and good physical properties are achieved.
Patent Information
- Application Number
- CN202411693002.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing multi-stage electrolytic technology for preparing electrolytic cobalt is difficult to effectively remove impurities in cobalt-containing solid raw materials, resulting in low cobalt purity.
The modified nanofiltration membrane was used for filtration, combined with hydrogen peroxide and polyacrylamide treatment, and further removed impurities and improved the purity of cobalt through multiple electrolysis and nitrogen purge.
The preparation of high-purity electrolytic cobalt is achieved, and the product has a uniform deposition layer, smooth surface, no cracks, no pores, and has good physical properties.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrometallurgy and relates to a method for preparing electrolytic cobalt by adopting multi-stage electrolysis. Background Art
[0002] Electrolytic cobalt is a high-purity, high-quality cobalt material that is widely used in precision instruments, cemented carbide, welding industry, lithium batteries, thermocouples, high-strength steel alloys, powder metallurgy and other fields. Especially in the automotive, aviation, medical, chemical and energy industries, electrolytic cobalt has become an important material for manufacturing key components due to its excellent corrosion resistance and stability under high temperature and high pressure environments.
[0003] Multi-stage electrolysis to prepare electrolytic cobalt is a technology that improves the purity of cobalt through multiple electrolytic refining processes. In the preparation process, the cobalt-containing raw materials are first converted into a cobalt salt solution through steps such as crushing and dissolution, and then multi-stage electrolysis is carried out through a series of electrolytic cells. Each stage of electrolysis is aimed at removing impurity ions in the solution, improving the purity of cobalt ions, and finally depositing high-purity electrolytic cobalt on the cathode. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing electrolytic cobalt by multi-stage electrolysis, which has the characteristics of high purity.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A method for preparing electrolytic cobalt by multi-stage electrolysis, wherein the specific process of preparing electrolytic cobalt is as follows:
[0007] S1: crushing the cobalt-containing solid raw material, grinding it in a ball mill at a speed of 500-600 r / min for 4-5 h to obtain powder A;
[0008] S2: dissolving powder A in a 10% by mass inorganic acid solution, wherein the solid-liquid mass ratio of powder A to the inorganic acid solution is 1:(5-10), to obtain a mixed solution B;
[0009] S3: passing the mixed solution B through a modified nanofiltration membrane, collecting the concentrated solution, adding 1-2 wt% hydrogen peroxide to the concentrated solution, stirring for 1-2 h, adding 1 wt% polyacrylamide after the stirring is completed, continuing to stir for 0.5 h, filtering, and obtaining a mixed solution C;
[0010] S4: injecting the mixed solution C into the electrolytic cell, and performing the first electrolysis using an insoluble anode to obtain crude electrolytic cobalt;
[0011] S5: The crude electrolytic cobalt obtained by the primary electrolysis is washed with deionized water, and then dried at 80° C. for 8 hours to remove impurities and moisture attached to the surface;
[0012] S6: performing secondary electrolysis on the crude electrolytic cobalt, wherein the electrolytic solution is a 10% by mass sulfuric acid-hydrochloric acid mixed acid solution, using metallic cobalt as a cathode and the crude electrolytic cobalt as an anode to further remove impurities and obtain high-purity electrolytic cobalt;
[0013] S7: The obtained electrolytic cobalt is purged with nitrogen for 12 hours, and then crushed and ground to obtain the electrolytic cobalt.
[0014] Furthermore, the inorganic acid solution in S2 is one of nitric acid, sulfuric acid and hydrochloric acid.
[0015] Furthermore, the preparation method of the modified nanofiltration membrane in S3 is as follows:
[0016] S3.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution D having a mass fraction of 20%;
[0017] S3.2: Mixing the graphene oxide solution D and the carboxybetaine solution having a mass fraction of 50% in a volume ratio of 1:1 to obtain a mixed solution E;
[0018] S3.3: Soak the polyamide membrane in the mixed solution E for 12 hours at a temperature of 40° C. After soaking, dry the membrane at room temperature to obtain the modified nanofiltration membrane.
[0019] Furthermore, the passing pressure of the modified nanofiltration membrane in S3 is 0.25-1 MPa.
[0020] Furthermore, the insoluble anode material in S4 is one of carbon, lead, graphite and stainless steel.
[0021] Furthermore, the first electrolysis parameters in S4 are electrolysis temperature 55-65°C, current density 300-400A / m 2 , electrolysis voltage 1.6 ~ 2.2V, electrolysis time is 3 ~ 4h.
[0022] Furthermore, in the sulfuric acid-hydrochloric acid mixed acid solution in S6, the volume ratio of sulfuric acid to hydrochloric acid is 1:1.
[0023] Furthermore, the second electrolysis parameters in S6 are electrolysis temperature 50-65°C, current density 400-500A / m 2 The electrolysis voltage is 1.8-2.0V and the electrolysis time is 4-6h.
[0024] Furthermore, the purge flow rate of nitrogen in S7 is 10 m / s.
[0025] The invention effectively removes impurities in the cobalt-containing solid raw material through multi-stage electrolytic purification treatment to obtain high-purity electrolytic cobalt; the electrolytic cobalt obtained by the method has a uniform deposition layer, a smooth surface, no cracks, no pores, and good physical properties.
[0026] The present invention first crushes and processes the cobalt-containing solid raw material, and the common solid raw materials are copper-cobalt ore and nickel-cobalt ore, and obtains the powder by fully grinding. This step increases the contact area between the raw material and the inorganic acid solution, and improves the dissolution efficiency. The cobalt-containing solid powder is dissolved in the inorganic acid solution to form a mixed solution containing cobalt ions, which provides the necessary electrolyte for the subsequent electrolysis process. The present invention effectively removes the impurity ions in the mixed solution by filtering with a modified nanofiltration membrane, adding hydrogen peroxide and polyacrylamide, and improving the purity of the cobalt ions. The first electrolysis step uses an insoluble anode for electrolysis, and crude electrolytic cobalt can be deposited on the cathode, thereby achieving the preliminary purification of cobalt. The second electrolysis uses a sulfuric acid-hydrochloric acid mixed acid solution as an electrolyte, further removing impurities in the crude electrolytic cobalt, and obtaining high-purity electrolytic cobalt. Finally, the residual gas and impurities on the surface of the electrolytic cobalt are removed by nitrogen purging, and the crushing and grinding make the electrolytic cobalt reach the required particle size requirements, thereby improving the quality and application value of the product.
[0027] The modified nanofiltration membrane has a finer filtration pore size and a more excellent separation performance, and can effectively intercept tiny particles and impurity ions in the solution, thereby improving the filtration efficiency. The surface properties of the nanofiltration membrane are improved through modification treatment, and the adsorption and deposition of pollutants on the membrane surface are reduced, thereby enhancing the pollution resistance of the membrane. The modified nanofiltration membrane has better selective permeability to cobalt ions and other impurity ions, and can more effectively retain cobalt ions during the filtration process while removing impurities.
[0028] Graphene oxide has abundant oxygen-containing functional groups, such as hydroxyl and carboxyl groups, which can interact with the surface of nanofiltration membranes to improve the hydrophilicity and separation performance of the membranes. Carboxybetaine is a zwitterionic compound with good anti-pollution properties. After mixing it with graphene oxide, it can further improve the surface properties of the nanofiltration membrane and reduce the adsorption of pollutants on the membrane surface. The mixed solution of graphene oxide and carboxybetaine can be evenly coated on the surface of the nanofiltration membrane, and combined with the membrane surface through physical adsorption and chemical bonding to form a modified layer. This modified layer not only improves the filtration accuracy and separation performance of the nanofiltration membrane, but also enhances its pollution resistance and selective permeability.
[0029] As a strong oxidant, hydrogen peroxide can effectively oxidize some impurity ions in the solution. Therefore, through the oxidation effect of hydrogen peroxide, a redox reaction occurs with the impurity ions, converting them into a form that is easier to remove, or directly precipitating them, thereby purifying the solution. It can further purify the cobalt salt solution and improve the purity of cobalt ions, which also creates more favorable conditions for the subsequent electrolysis process. Polyacrylamide is a polymer flocculant. After being added to the mixed solution, it can aggregate the tiny particles and impurity ions in the solution into larger flocs through adsorption, bridging and other effects, which is convenient for subsequent filtration operations, and at the same time further purifies the cobalt salt solution and improves the purity of cobalt ions.
[0030] The first electrolysis can reduce the cobalt ions in the purified cobalt salt solution to metallic cobalt at the cathode to obtain crude electrolytic cobalt. Through the electrolysis process, the cobalt ions in the solution can be effectively converted into metallic cobalt, achieving the initial purification of cobalt. At the same time, the electrolysis process can also remove some impurities and improve the purity of cobalt; during the electrolysis process, a reduction reaction occurs at the cathode, and the cobalt ions accept electrons and are reduced to metallic cobalt. Due to the selectivity of electrolysis, most impurity ions will not be reduced at the cathode, thereby achieving the separation of cobalt and impurities.
[0031] The second electrolysis can further remove impurities in the crude electrolytic cobalt to obtain electrolytic cobalt with higher purity; the crude electrolytic cobalt can be further purified by the secondary electrolysis, and trace impurities can be removed to obtain electrolytic cobalt with higher purity. This helps to improve the quality and application value of electrolytic cobalt; in the secondary electrolysis process, a sulfuric acid-hydrochloric acid mixed acid solution is used as an electrolyte, which has a certain dissolving capacity for impurities. At the same time, due to the selectivity of electrolysis, impurity ions may undergo oxidation reactions at the anode and be removed, while cobalt ions are reduced to metallic cobalt at the cathode. Through the further purification effect of the secondary electrolysis, electrolytic cobalt with higher purity can be obtained.
[0032] Beneficial effects of the present invention:
[0033] (1) The modified nanofiltration membrane used in the preparation process of the present invention has a finer filtration pore size and more excellent separation performance, and can effectively intercept tiny particles and impurity ions in the solution, thereby improving the filtration efficiency. Through the modification treatment, the surface properties of the nanofiltration membrane are improved, and the adsorption and deposition of pollutants on the membrane surface are reduced, thereby enhancing the pollution resistance of the membrane. The modified nanofiltration membrane has better selective permeability to cobalt ions and other impurity ions, and can more effectively retain cobalt ions during the filtration process while removing impurities;
[0034] (2) The present invention effectively removes impurities in the cobalt-containing solid raw material through multi-stage electrolytic purification treatment, thereby obtaining electrolytic cobalt with higher purity. DETAILED DESCRIPTION
[0035] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0036] Example 1
[0037] S1: The copper-cobalt ore is crushed and ground in a ball mill at a speed of 550 r / min for 5 h to obtain powder A;
[0038] S2: dissolving powder A in a 10% by mass nitric acid solution, wherein the solid-liquid mass ratio of powder A to the inorganic acid solution is 1:8, to obtain a mixed solution B;
[0039] S3: passing the mixed solution B through a modified nanofiltration membrane with a passing pressure of 0.5 MPa, collecting the concentrated solution, adding 1 wt% hydrogen peroxide to the concentrated solution, stirring for 1 hour, adding 1 wt% polyacrylamide after the stirring is completed, continuing to stir for 0.5 hours, filtering, and obtaining a mixed solution C;
[0040] The modified nanofiltration membrane preparation method is as follows:
[0041] S3.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution D having a mass fraction of 20%;
[0042] S3.2: Mixing the graphene oxide solution D and the carboxybetaine solution having a mass fraction of 50% in a volume ratio of 1:1 to obtain a mixed solution E;
[0043] S3.3: Soak the polyamide membrane in the mixed solution E for 12 hours at a temperature of 40° C. After soaking, dry the membrane at room temperature to obtain the modified nanofiltration membrane.
[0044] S4: Inject the mixed solution C into the electrolytic cell and use insoluble anode graphite for the first electrolysis. The first electrolysis parameters are electrolysis temperature 60°C, current density 350A / m 2 , electrolysis voltage 2V, electrolysis time 3h, to obtain crude electrolytic cobalt;
[0045] S5: The crude electrolytic cobalt obtained by the primary electrolysis is washed with deionized water, and then dried at 80° C. for 8 hours to remove impurities and moisture attached to the surface;
[0046] S6: The crude electrolytic cobalt is subjected to secondary electrolysis. The parameters of the second electrolysis are electrolysis temperature 65°C and current density 450A / m 2, the electrolysis voltage is 1.8V, the electrolysis time is 4h, the electrolytic solution is a 10% sulfuric acid-hydrochloric acid mixed acid solution, wherein the volume ratio of sulfuric acid to hydrochloric acid is 1:1, metallic cobalt is used as the cathode, and the crude electrolytic cobalt is used as the anode to further remove impurities and obtain high-purity electrolytic cobalt;
[0047] S7: The obtained electrolytic cobalt is purged with nitrogen at a purging flow rate of 10 m / s for 12 h. After purging, the obtained electrolytic cobalt is crushed and ground to obtain the electrolytic cobalt.
[0048] Example 2
[0049] S1: crushing the nickel-cobalt ore and grinding it in a ball mill at a speed of 500 r / min for 4 h to obtain powder A;
[0050] S2: dissolving powder A in a 10% sulfuric acid solution, wherein the solid-liquid mass ratio of powder A to the inorganic acid solution is 1:10, to obtain a mixed solution B;
[0051] S3: passing the mixed solution B through a modified nanofiltration membrane with a passing pressure of 1 MPa, collecting the concentrated solution, adding 2 wt% hydrogen peroxide to the concentrated solution, stirring for 2 h, adding 1 wt% polyacrylamide after stirring, continuing stirring for 0.5 h, filtering, and obtaining a mixed solution C;
[0052] The modified nanofiltration membrane preparation method is as follows:
[0053] S3.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution D having a mass fraction of 20%;
[0054] S3.2: Mixing the graphene oxide solution D and the carboxybetaine solution having a mass fraction of 50% in a volume ratio of 1:1 to obtain a mixed solution E;
[0055] S3.3: Soak the polyamide membrane in the mixed solution E for 12 hours at a temperature of 40° C. After soaking, dry the membrane at room temperature to obtain the modified nanofiltration membrane.
[0056] S4: Inject the mixed solution C into the electrolytic cell and use insoluble anode stainless steel for the first electrolysis. The first electrolysis parameters are electrolysis temperature 55°C, current density 300A / m 2 , electrolysis voltage 1.6V, electrolysis time 4h, to obtain crude electrolytic cobalt;
[0057] S5: The crude electrolytic cobalt obtained by the primary electrolysis is washed with deionized water, and then dried at 80° C. for 8 hours to remove impurities and moisture attached to the surface;
[0058] S6: The crude electrolytic cobalt is subjected to secondary electrolysis. The parameters of the second electrolysis are electrolysis temperature of 50°C and current density of 400A / m 2 , the electrolysis voltage is 1.8V, the electrolysis time is 6h, the electrolytic solution is a 10% sulfuric acid-hydrochloric acid mixed acid solution, wherein the volume ratio of sulfuric acid to hydrochloric acid is 1:1, metallic cobalt is used as the cathode, and the crude electrolytic cobalt is used as the anode to further remove impurities and obtain high-purity electrolytic cobalt;
[0059] S7: The obtained electrolytic cobalt is purged with nitrogen at a purging flow rate of 10 m / s for 12 h. After purging, the obtained electrolytic cobalt is crushed and ground to obtain the electrolytic cobalt.
[0060] Example 3
[0061] S1: The copper-cobalt ore is crushed and ground in a ball mill at a speed of 600 r / min for 4 h to obtain powder A;
[0062] S2: dissolving powder A in a 10% hydrochloric acid solution, wherein the solid-liquid mass ratio of powder A to the inorganic acid solution is 1:5, to obtain a mixed solution B;
[0063] S3: passing the mixed solution B through a modified nanofiltration membrane with a passing pressure of 0.25 Pa, collecting the concentrated solution, adding 1 wt% hydrogen peroxide to the concentrated solution, stirring for 1 hour, adding 1 wt% polyacrylamide after stirring, continuing stirring for 0.5 hours, filtering, and obtaining a mixed solution C;
[0064] The modified nanofiltration membrane preparation method is as follows:
[0065] S3.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution D having a mass fraction of 20%;
[0066] S3.2: Mixing the graphene oxide solution D and the carboxybetaine solution having a mass fraction of 50% in a volume ratio of 1:1 to obtain a mixed solution E;
[0067] S3.3: Soak the polyamide membrane in the mixed solution E for 12 hours at a temperature of 40° C. After soaking, dry the membrane at room temperature to obtain the modified nanofiltration membrane.
[0068] S4: Inject the mixed solution C into the electrolytic cell and use insoluble anode graphite for the first electrolysis. The first electrolysis parameters are electrolysis temperature 65°C, current density 400A / m 2 , electrolysis voltage 2.2V, electrolysis time 3h, to obtain crude electrolytic cobalt;
[0069] S5: The crude electrolytic cobalt obtained by the primary electrolysis is washed with deionized water, and then dried at 80° C. for 8 hours to remove impurities and moisture attached to the surface;
[0070] S6: The crude electrolytic cobalt is subjected to secondary electrolysis. The parameters of the second electrolysis are electrolysis temperature 65°C and current density 500A / m 2 , the electrolysis voltage is 2.0V, the electrolysis time is 4h, the electrolytic solution is a 10% sulfuric acid-hydrochloric acid mixed acid solution, wherein the volume ratio of sulfuric acid to hydrochloric acid is 1:1, metallic cobalt is used as the cathode, and the crude electrolytic cobalt is used as the anode to further remove impurities and obtain high-purity electrolytic cobalt;
[0071] S7: The obtained electrolytic cobalt is purged with nitrogen at a purging flow rate of 10 m / s for 12 h. After purging, the obtained electrolytic cobalt is crushed and ground to obtain the electrolytic cobalt.
[0072] Comparative Example 1
[0073] This comparative example does not use a modified nanofiltration membrane, and the remaining steps are consistent with Example 1.
[0074] Comparative Example 2
[0075] In this comparative example, no graphene oxide solution was added during the preparation of the modified nanofiltration membrane, and the remaining steps were consistent with Example 1.
[0076] Comparative Example 3
[0077] In this comparative example, no carboxybetaine solution was added during the preparation of the modified nanofiltration membrane, and the remaining steps were consistent with Example 1.
[0078] Comparative Example 4
[0079] In this comparative example, no hydrogen peroxide was added during the preparation process, and the remaining steps were consistent with those in Example 1.
[0080] Comparative Example 5
[0081] In this comparative example, no polyacrylamide was added during the preparation process, and the remaining steps were consistent with those in Example 1.
[0082] Comparative Example 6
[0083] In the preparation process of this comparative example, no secondary electrolysis was performed, and the remaining steps were consistent with those of Example 1.
[0084] The purity of the electrolytic cobalt obtained in the embodiment and the comparative example was tested, and the experimental results are summarized in the following table:
[0085] Electrolytic cobalt purity (%) Example 1 99.9 Example 2 99.8 Example 3 99.8 Comparative Example 1 94.7 Comparative Example 2 95.5 Comparative Example 3 95.9 Comparative Example 4 96.4 Comparative Example 5 96.8 Comparative Example 6 92.3
[0086] It can be seen from the data of the examples and comparative examples that modification of the nanofiltration membrane, addition of hydrogen peroxide and polyacrylamide during the preparation process, and multiple electrolysis all result in higher purity of the electrolytic cobalt obtained.
[0087] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing electrolytic cobalt by multi-stage electrolysis, characterized in that: The specific process of electrolytic cobalt preparation is as follows: S1: crushing the cobalt-containing solid raw material, grinding it in a ball mill at a speed of 500-600 r / min for 4-5 h to obtain powder A; S2: dissolving powder A in a 10% by mass inorganic acid solution, wherein the solid-liquid mass ratio of powder A to the inorganic acid solution is 1:(5-10), to obtain a mixed solution B; S3: passing the mixed solution B through a modified nanofiltration membrane, collecting the concentrated solution, adding 1-2 wt% hydrogen peroxide to the concentrated solution, stirring for 1-2 h, adding 1 wt% polyacrylamide after the stirring is completed, continuing to stir for 0.5 h, filtering, and obtaining a mixed solution C; S4: injecting the mixed solution C into the electrolytic cell, and performing the first electrolysis using an insoluble anode to obtain crude electrolytic cobalt; S5: The crude electrolytic cobalt obtained by the primary electrolysis is washed with deionized water, and then dried at 80° C. for 8 hours to remove impurities and moisture attached to the surface; S6: performing secondary electrolysis on the crude electrolytic cobalt, wherein the electrolytic solution is a 10% by mass sulfuric acid-hydrochloric acid mixed acid solution, using metallic cobalt as a cathode and the crude electrolytic cobalt as an anode to further remove impurities and obtain high-purity electrolytic cobalt; S7: The obtained electrolytic cobalt is purged with nitrogen for 12 hours, and then crushed and ground to obtain the electrolytic cobalt.
2. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: The inorganic acid solution in S2 is one of nitric acid, sulfuric acid and hydrochloric acid.
3. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: The preparation method of the modified nanofiltration membrane in S3 is as follows: S3.1: dissolving graphene oxide in deionized water to prepare a graphene oxide solution D having a mass fraction of 20%; S3.2: Mixing the graphene oxide solution D and the carboxybetaine solution having a mass fraction of 50% in a volume ratio of 1:1 to obtain a mixed solution E; S3.3: Soak the polyamide membrane in the mixed solution E for 12 hours at a temperature of 40° C. After soaking, dry the membrane at room temperature to obtain the modified nanofiltration membrane.
4. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: The passing pressure of the modified nanofiltration membrane in S3 is 0.25-1 MPa.
5. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: The insoluble anode material in S4 is one of carbon, lead, graphite and stainless steel.
6. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: The first electrolysis parameters in S4 are electrolysis temperature 55-65°C, current density 300-400A / m 2 , electrolysis voltage 1.6 ~ 2.2V, electrolysis time is 3 ~ 4h.
7. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: In the sulfuric acid-hydrochloric acid mixed acid solution in S6, the volume ratio of sulfuric acid to hydrochloric acid is 1:
1.
8. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: The second electrolysis parameters in S6 are electrolysis temperature 50-65°C, current density 400-500A / m 2 The electrolysis voltage is 1.8-2.0V and the electrolysis time is 4-6h.
9. The method for preparing electrolytic cobalt by multi-stage electrolysis according to claim 1, characterized in that: The purge flow rate of nitrogen in S7 is 10 m / s.
Citation Information
Patent Citations
Method for producing electrolytic cobalt through secondary electrolysis of cobalt intermediate product
CN113026056A
Process for efficiently treating cold rolling chromium-containing wastewater
CN118724392A